(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Background: To date, the mechanisms linking components underlying the cardiometabolic syndrome (also known metabolic syndrome) remain unclear and other investigators have suggested that inflammation plays a primary pathogenic role. Pro-inflammatory cytokines including IL-6 and tumor necrosis factor alpha (TNF- α) are released from macrophages within the vessel wall during an inflammatory response. These cytokines mediate distant inflammatory effects, including activation of hepatic genes encoding acute phase reactant CRP. Purpose: This study aimed to evaluate the levels of these pro-inflammatory markers in Egyptian obese and diabetic subjects and their correlation with metabolic syndrome. Results: Our results showed that there were statistically significant differences among studied groups in the inflammatory markers (hs- CRP, IL-6 & TNF- α), being higher in obese and diabetics. Significant positive correlation was seen between inflammatory markers and most of metabolic syndrome markers. Conclusion: Our results are confirming the role of pro-inflammatory markers in the development and pathogenesis of metabolic syndrome in Egyptians.